2017
DOI: 10.1155/2017/3264098
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Extruded Poly(lactic acid)/Pecan Nutshell Biocomposites

Abstract: Pecan nutshells are a solid form of waste obtained from the pecan nut production and they have been explored as an inexpensive filler for incorporation by melt blending into the poly(lactic acid) (PLA) matrix. The pecan nutshells contain polyphenols, proteins, tannins, sugars, and lipids; some of these components must be released in order to improve adhesion with a polymeric matrix. The physicochemical characterization of the extruded biocomposites of pecan nutshell powder (PNSP) at 0, 5, and 7.5% wt. with two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…The HSPs’ addition increases the crystallinity of the PLA, causing a shift of the cold crystallization temperature towards lower temperatures. HSP seems to act as a nucleating agent, providing heterogeneous nucleation sites similar to other systems filled with natural fibers [ 27 , 47 , 48 ]. In particular, as the HM200 are finer and more homogeneous with a tighter diameter distribution curve, they are more effective in crystallizing the PLA, when compared to their H0210 counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…The HSPs’ addition increases the crystallinity of the PLA, causing a shift of the cold crystallization temperature towards lower temperatures. HSP seems to act as a nucleating agent, providing heterogeneous nucleation sites similar to other systems filled with natural fibers [ 27 , 47 , 48 ]. In particular, as the HM200 are finer and more homogeneous with a tighter diameter distribution curve, they are more effective in crystallizing the PLA, when compared to their H0210 counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…Other researchers stated that pecan nutshells could be a reinforcing filler in polymer-based biocomposites once it presents good dispersion and adhesion to a PLA matrix [31]. Moreover, biocomposites added with pecan nutshells could be applied as food containers, packaging trays, or disposable items [32].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have indicate the application of this technique in pecan waste materials, mainly aiming at characterizing the physicochemical composition and obtaining properties that present activity against pathogens of these residues. Studies have shown that the application of this method and methane as a solvent allowed a detailed analysis of the pecan shell composition, characterizing the phenolic compounds, tannins and lipids present in these materials, as well as a morphological evaluation of their structure [53]. In addition, the obtaining of antioxidant materials from pecan shells by the Soxhlet and methane method as a solvent was effective in inhibiting the activity of a range of bacterial microorganisms [54].…”
Section: Compounds Extractionmentioning
confidence: 99%